Investigation into rapid (alternative) microbial detection methods to improve the quality assurance of NHS manufactured aseptic products. Issue 2 (12th March 2012) - Hiom, S.; Talbot, C.; Spark, P.; Smith, J.; Denyer, S.D.
Abstract : Background: Real-time QA is a challenge for short-expiry, high-risk aseptic products and is often retrospective. There are documented examples of quality failure with aseptic manufacture. Rapid microbiological methods (RMMs) have been used in the pharmaceutical and food industry for many years and early pilot work from our group with aseptic national health service (NHS) products has been encouraging. Purpose: To evaluate three commercial RMM technologies for their ability to improve the traditional QA processes associated with NHS aseptic manufactured products. Materials and methods: The three commercial RMM systems evaluated were BacT/ALERT (bioMerieux), AkuScreen (Celsis) and BactiFlow ALS (AES Chemunex). A deliberate contamination study was carried out in which 50 µl of four microbes was inoculated into four aseptic products (heparin 100 u/ml; parenteral nutrition (PN) 7.5%; vancomycin inj. 10 mg/2 ml and methotrexate inj. 15 mg/0.6 ml) and left for 10 min (final concentration 10–100 CFU/ml). Total aerobic microbial counts (TAMC) were compared with RMM results. All work was carried out in a Grade A environment. Results: The recovery rates are presented below as percentage concordance together with time to detection. All three RMM systems were able to provide 100% concordance when used to detect contamination in PN and heparin within their recommended time frames. All rapid methods had problems recovering Gram +ve organisms from vancomycin and methotrexate, although recovery of other organisms from these products was equivalent. The BacT/ALERT system was technically the easiest to use and had the highest concordance when results were read after 3 days. Conclusions: The authors believe this data describes a true reflection of the alternative rapid detection methods and demonstrates that RMM can improve QA of selected NHS manufactured aseptic products.